Influential Evaluations : Evaluations that Improved Performance and Impacts of Development Programs - Operations Evaluation Department (World Bank, Washington, DC, 2016)
This report presents 8 examples of evaluations that had a significant impact. In many cases it was possible to compare the costs of conducting the evaluation with the economic benefits produced and to show that the evaluation was a highly cost-effective management tool. The cases describe the following evaluations: Improving the efficiency of the Indian employment assurance scheme; Using citizen report cards to hold the state to account in Bangalore, India; Assessing the effectiveness of water and sanitation interventions in Flores, Indonesia; Broadening the policy framework for assessing the viability of large dams; The abolition of wheat-flour ration shops in Pakistan; Improving the delivery of primary education services in Uganda; Enhancing the performance of a major environmental project in Bulgaria; Helping re-assess China's national forest policy.